1987
DOI: 10.2527/jas1987.6441044x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Level of Protein and Supplemental Choline on Reproductive Performance of Gilts Fed Sorghum Diets

Abstract: A total of 214 gilts was used (two trials) to determine the effect of protein level and choline supplementation during gestation on weight gain, conception rate and subsequent reproductive performance. The gihs were fed either a 12 or 16% crude protein sorghum-soybean meal diet containing either a high supplemental choline level or no supplemental choline in a 2 • 2 factorial arrangement of treatments Conception rate was not influenced by either protein or choline level. Choline ~pplementation increased pig we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

1991
1991
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 29 publications
0
1
1
Order By: Relevance
“…PCS symptoms apparently disappeared after injection of the acetylcholine esterase blocker neostigmine-methylsulfate (21). However, these results could not be confirmed in other studies (48,49). Furthermore, neither choline plasma levels nor activities of various choline esterases were found to be reduced in PCS piglets (44).…”
Section: Current Statuscontrasting
confidence: 62%
See 1 more Smart Citation
“…PCS symptoms apparently disappeared after injection of the acetylcholine esterase blocker neostigmine-methylsulfate (21). However, these results could not be confirmed in other studies (48,49). Furthermore, neither choline plasma levels nor activities of various choline esterases were found to be reduced in PCS piglets (44).…”
Section: Current Statuscontrasting
confidence: 62%
“…This was supported by positive effects of the administration of the acetylcholine esterase blocker neostigmine-methylsulfate on the incidence of PCS (21). However, these results have not been confirmed in other studies (44,48,49). In contrast, it was shown that PCS-affected animals showed significantly increased acetylcholine esterase activities in cerebellum, brain stem and spinal cord (50).…”
Section: Biochemical Characteristicsmentioning
confidence: 77%